WATERBORNE INFECTIOUS DISEASES: A PERSISTENT CHALLENGE TO PUBLIC HEALTH - Bahriniso Isodukht (Interdisciplinary Approaches to Medicine, 2025)
Introduction: Waterborne diseases remain a significant public health issue, particularly in regions with poor sanitation and limited access to clean water. In Tajikistan, these diseases, especially among children, are a major concern. Water scarcity and pollution, exacerbated by climate change, contribute to the problem.